The Role of Non-coding RNAs as an Innovative Therapeutic Tool for Hepatocellular Carcinoma - El kramani, Nabila Mohamed Hosni (AUC Knowledge Fountain, 2025)
Hepatocellular carcinoma (HCC) is the second lethal cancer worldwide, with over 60 million new patients added annually. Hepatitis B infection and toxins, e.g., aflatoxin, contribute to the incidence of HCC. Egypt and China show the highest prevalence of viral hepatitis and HCC in the world. Long non-coding RNAs (lncRNAs) are non-protein-coding transcripts larger than 200 nucleotides. These transcripts work at the transcriptional, post-transcriptional, and epigenetic levels to regulate gene expression by interacting with various biomolecules, such as RNA, DNA, and proteins. They serve essential functions in chromatin remodeling and cell survival, differentiation, and proliferation. The role and biological interactions of lncRNAs, especially in HCC, are complex. Evidence suggests that aberrant expression of lncRNAs is linked to the incidence, invasiveness, and metastasis of HCC. LncRNAs also have potential use as markers for early detection of HCC. The majority of HCC cases are discovered late at an advanced stage due to the lack of early diagnostic markers. Studies suggest that the diagnostic accuracy of lncRNAs may be affected by many factors, including viral co-infections of patients with HCC. However, differences in the diagnostic accuracy of lncRNAs between Asian and African countries are not statistically significant. The roles of lncRNAs in HCC have been reported to be associated with tumor growth and proliferation (such as HULC, MEG3, CCAT1, PVT1, and PTENP1) and associated with metastasis and prognosis (such as H19, MALAT1, HOTAIR, HOTTIP, HEIH, and lncRNA-p21). This study investigates the potential role of some lncRNAs that are known to be aberrantly expressed in human HCC tissues to identify suitable candidates for future use as diagnostic, prognostic, and therapeutic tools in HCC.